Nurse – patient communication: an exploration of nurses’ experiences - Meižytė, Karolina; Blaževičienė, Aurelija (Slauga. Mokslas ir praktika, 2022)
A good relationship between a nurse and a patient is considered particularly important in a nurse's professional path and one of the main components of good nursing. Effective relationships based on mutual understanding lead to patient satisfaction and the determination of individual nursing care measures. The patient tends to be more involved in his treatment process and to trust the health care professional.Aim. To assess the quality of communication between nurses and patients from the perspective of nurses.Methods. A quantitative study was conducted using an anonymous online questionnaire. Research participants are general practice nurses working in Lithuanian health care institutions (n - 231). The standardized questionnaire The Nurse Quality of Communication with Patient Questionnaire (NQCPQ) was used to collect research data.Results and conclusions. Nurses indicate that the higher quality of communication with the patient allows the patient to open up and speak more confidently about his illness (84.4%, n = 195) and at the same time the nurse can better understand the seriousness of the patient's health and communicate about it (84.0%, n = 194). High-quality communication between the nurse and the patient helps the specialist understand that the prescribed drug treatment is acceptable to the patient (80.1%, n = 185). Nurses can decide on the appropriateness of treatment for the patient based only on the patient's reactions (71.9%, n = 166) and nurses can only assess the patient's current state of health by observing the patient (68.4%, n = 158).The quality of communication between nurses and patients determines the ability of nurses to assess the patient's state of health, decide on the appropriateness of the prescribed treatment, and the quality of communication affects communication with the patient during procedures, hygiene and nutrition.
Keywords: nurse-patient communication; communication; nursing